2012
DOI: 10.2214/ajr.11.7798
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Estimations to the Thorax Using Organ-Based Dose Modulation

Abstract: Organ-based dose modulation CT using an anterior 120° arc can reduce the organ dose in the anterior aspect of the thorax with a compensatory organ dose increase posteriorly without impairment of image quality. Laterally located breast tissue will have higher organ doses than medially located breast tissue when using organ-based dose modulation. The benefit of this dose reduction must be clinically determined on the basis of the relationship of the irradiated organs to the location of the prescribed radial arc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 22 publications
4
45
1
Order By: Relevance
“…33 We found that maternal breast dose is generally higher for CTPA than for VQ, but organ-based tube current modulation has been shown to reduce this. 35 Further opportunities to reduce CTPA radiation doses include the use of statistical and model-based iterative reconstruction techniques, 36 reducing the tube voltage, as we have already performed from 120 to 100 kVp, 37 increasing the pitch to above 1 and decreasing the scan volume. Lowering the peak kilovoltage has the additional advantage of increasing the contrast attenuation within the pulmonary arteries, as the average X-ray energy approaches the k-edge of iodine (33 keV).…”
Section: Dosimetrymentioning
confidence: 99%
“…33 We found that maternal breast dose is generally higher for CTPA than for VQ, but organ-based tube current modulation has been shown to reduce this. 35 Further opportunities to reduce CTPA radiation doses include the use of statistical and model-based iterative reconstruction techniques, 36 reducing the tube voltage, as we have already performed from 120 to 100 kVp, 37 increasing the pitch to above 1 and decreasing the scan volume. Lowering the peak kilovoltage has the additional advantage of increasing the contrast attenuation within the pulmonary arteries, as the average X-ray energy approaches the k-edge of iodine (33 keV).…”
Section: Dosimetrymentioning
confidence: 99%
“…1) [7]. Recent publications indicated that in a majority of women in the supine position, a portion of glandular breast tissue is located outside the reduced dose zone and therefore might be under increased risk of over-irradiation even when using organ-based tube current modulation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth breast shielding was previously reported to reduce radiation exposure to the breasts by approximately 30 without affecting images 2,[6][7][8][9] ; now this study indicates that X-CARE could be used as a viable alternative. In atomic bomb survivors the radiation dose-response relationship for breast cancer is linear, with a relative risk per Gray of 1.9 10 .…”
Section: Discussionmentioning
confidence: 64%